Identification of transcription factors responsible for dysregulated networks in human osteoarthritis cartilage by global gene expression analysis. Issue 11 (November 2018) - Fisch, K.M.; Gamini, R.; Alvarez-Garcia, O.; Akagi, R.; Saito, M.; Muramatsu, Y.; Sasho, T.; Koziol, J.A.; Su, A.I.; Lotz, M.K.
Summary: Objective: Osteoarthritis (OA) is the most prevalent joint disease. As disease-modifying therapies are not available, novel therapeutic targets need to be discovered and prioritized for their importance in mediating the abnormal phenotype of cells in OA-affected joints. Here, we generated a genome-wide molecular profile of OA to elucidate regulatory mechanisms of OA pathogenesis and to identify possible therapeutic targets using integrative analysis of mRNA-sequencing data obtained from human knee cartilage. Design: RNA-sequencing (RNA-seq) was performed on 18 normal and 20 OA human knee cartilage tissues. RNA-seq datasets were analysed to identify genes, pathways and regulatory networks that were dysregulated in OA. Results: RNA-seq data analysis revealed 1332 differentially expressed (DE) genes between OA and non-OA samples, including known and novel transcription factors (TFs). Pathway analysis identified 15 significantly perturbed pathways in OA with ECM-related, PI3K-Akt, HIF-1, FoxO and circadian rhythm pathways being the most significantly dysregulated. We selected DE TFs that are enriched for regulating DE genes in OA and prioritized these TFs by creating a cartilage-specific interaction subnetwork. This analysis revealed eight TFs, including JUN, Early growth response (EGR)1, JUND, FOSL2, MYC, KLF4, RELA, and FOS that both target large numbers of dysregulated genes in OA and are themselves suppressed in OA. Conclusions: We identified a novel subnetwork of dysregulated TFs that represent new mediators of abnormal gene expression and promising therapeutic targets in OA.